2021
DOI: 10.1002/eat.23563
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical brain volume and cortical thickness in adolescent girls and women with binge eating

Abstract: Objective: Alterations in brain structure have been implicated in the onset and acute phases of several forms of psychopathology. However, there is a dearth of research investigating brain structure in persons with binge eating, contributing to poor understanding of mechanisms associated with binge eating.Method: Adolescent girls and women (aged 14-35 years) with binge eating (n = 56) and group age-matched girls and women without binge eating (n = 26) completed structural magnetic resonance imaging (MRI) scans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…One recent study showed that the cortex in the right precentral gyrus in some progressive neurodegenerative disorders was becoming thinner such as amyotrophic lateral sclerosis 16 . The emotional eating disorder has also been related to the right precentral gyrus, symptoms being negatively correlated with the volume of the gyrus 17 . This region also featured in eye research, patients with iridocyclitis reportedly having a signi cantly lower the amplitude of low-frequency uctuation value in this region than healthy controls 18 .…”
Section: Discussionmentioning
confidence: 99%
“…One recent study showed that the cortex in the right precentral gyrus in some progressive neurodegenerative disorders was becoming thinner such as amyotrophic lateral sclerosis 16 . The emotional eating disorder has also been related to the right precentral gyrus, symptoms being negatively correlated with the volume of the gyrus 17 . This region also featured in eye research, patients with iridocyclitis reportedly having a signi cantly lower the amplitude of low-frequency uctuation value in this region than healthy controls 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with other neurological disorders, use of psychoactive medications, and other chronic diseases were excluded. Given the comorbidity between bulimia and overweight/obesity (e.g., Da Luz et al., 2018 ; Jebeile et al., 2021 ), and given that the sample was drawn from a general population, those with a BMI above/below normal weight were not excluded (e.g., Abdo et al., 2020 ; Hagan & Bohon, 2021 ) in order to maximize the number of participants and the ecological validity of the results. Instead, we included BMI as covariates to ensure that our results were not confounded by participants’ BMI.…”
Section: Methodsmentioning
confidence: 99%
“…To date, relatively few neuroimaging studies have assessed the neural circuits involved in the psychopathology of BED (Steward, Menchon, Jiménez-Murcia, Soriano-Mas, & Fernandez-Aranda, 2018), and those that exist have predominantly assessed adults. Existing studies of those engaging in binge eating episodes have revealed no consistent alterations in gray matter morphometry (Abdo, Boyd, Baboumian, Pantazatos, & Geliebter, 2020; Hagan & Bohon, 2021), although arterial spin labeling studies suggest that women with binge type eating disorder presentations (BED, BN) demonstrate increased regional cerebral blood flow in both reward and inhibitory control regions (Martins et al, 2020). Functional MRI (fMRI) studies have illustrated elevated OFC and VS activity during food cue presentation tasks (Lee, Namkoong, & Jung, 2017; Weygandt, Schaefer, Schienle, & Haynes, 2012), which predicts clinical BED symptom severity (Wang et al, 2011).…”
mentioning
confidence: 99%
“…Existing studies of those engaging in binge eating episodes have revealed no consistent alterations in gray matter morphometry (Abdo, Boyd, Baboumian, Pantazatos, & Geliebter, 2020;Hagan & Bohon, 2021), although arterial spin labeling studies suggest that women with binge type eating disorder presentations (BED, BN) demonstrate increased regional cerebral blood flow in both reward and inhibitory control regions (Martins et al, 2020). Functional MRI (fMRI) studies have illustrated elevated OFC and VS activity during food cue presentation tasks (Lee, Namkoong, & Jung, 2017;Weygandt, Schaefer, Schienle, & Haynes, 2012), which predicts clinical BED symptom severity (Wang et al, 2011).…”
mentioning
confidence: 99%